Linking the Historical Sample of the Netherlands with the USA Censuses, 1850–1940 - Diogo Paiva; Francisco Anguita; Kees Mandemakers (Historical Life Course Studies)
During the 19th and early 20th century about 220,000 Dutch born persons migrated to the USA. The Historical Sample of the Netherlands (HSN) contains about 85,500 persons born in the Netherlands between 1812 and 1922. In this article we report the way we have matched persons from the HSN with the American censuses from the period 1850 till 1940. For this purpose, a linking process was designed, comprising of three stages: harmonization, matching and validation. The different nature of the two datasets (HSN and the USA Censuses) asked for some harmonization prior to the matching. Once the data had been properly prepared, two strategies were applied in order to link the data sets. The first one, called Similarity Approach, matched individuals from both datasets by comparing on the basis of resemblance of first and last names. The second approach, called Transformation Approach, made use of dictionaries with Anglicized versions of Dutch first and last names and their most common or most likely Dutch original(s). Because of the sample character of the HSN even exact matches showed ambiguity that needs to be resolved. For this reason, a validation process comparing the household context was run to provide a more trustworthy result. In the end we identified 484 individuals present in the HSN database with reliable links to the American censuses. We also evaluated the result in the light of what we know from emigration patterns to the USA over time and period and we concluded that our efforts have produced a reasonable result. Nevertheless, we are aware that we may have missed links. We also found that at least 45% of the emigrants returned to the Netherlands at some point during their life course.